Decrease in Escherichia-Shigella in the gut microbiota of ESKD patients undergoing maintenance hemodialysis - Qin, Yunlong; Zhao, Jin; Wang, Lihui; Yang, Xinjun; Wang, Jinghua; Li, Shaojian; Chen, Yunshuang; Guo, Jiaming; Wang, Fang; Luo, Kaifa (BMC nephrology, 2025)
Background Gut dysbiosis is thought to be involved in the pathogenesis and progression of chronic kidney disease and end-stage kidney disease (ESKD). However, differences in the composition and function of gut microbiota in hemodialysis patients are not consistently concluded. Methods A total of 20 patients receiving maintenance hemodialysis (MHD) treatment at the Blood Purification Center of Bethune International Peace Hospital from March 2021 to December 2022 were included based on the inclusion criteria. Additionally, 20 healthy volunteers matched for age, gender, and body mass index were recruited from the Health Examination Center as the healthy control (HC) group. The structure of the gut microbiota community in the study subjects was analyzed using second-generation high-throughput sequencing technology based on 16S rRNA and amplicon sequence variants (ASV) analysis. Results There were significant differences in gut microbial communities between the two groups. At the genus level, significant differences were found in 19 genera. Among them, Escherichia-Shigella , Lachnospira , Parasutterella , [Ruminococcus]-torques-group , Butyricicoccus , and Streptococcus were significantly decreased, while Phascolarctobacterium , Ruminococcaceae-UBA1819 , Erysipelotrichaceae-UCG-003 , Flavonifractor , and Erysipelatoclostridium were significantly increased in MHD patients. In particular, the abnormal decrease in the abundance of p-Proteobacteria.c-Gammaproteobacteria.o-Enterobacterales.f-Enterobacteriaceae.g-Escherichia-Shigella might be a significant characteristic of gut microbiota in MHD patients. Conclusion The decreased abundance of Escherichia-Shigella is a signature gut microbiota alteration in patients with ESKD undergoing MHD, and Escherichia-Shigella may represent a key bacterial group warranting exploration in the field of hemodialysis. The dysbiosis of gut microbiota holds promise as a therapeutic target and biomarker for the diagnosis and treatment of MHD.